PRESENCE OF D CHELYDRAE IN A FRESHWATER TURTLE - CABALLERO Y C, EDUARDO; C, EDUARDO (Instituto de Estudios Médicos y Biológicos, CD MEXICO, DF, MEX, 1946)
In tests on the control of the citrus blackfly (Aleurocanthus woglumi) in Cuernavaca, Morelos, Mexico, trees were sprayed repeatedly with 5% kerosene emulsion and 075% light-medium emulsive oil, with and without 0375 lb of DDT in 100 gal of emulsion;
ANS INST BIOL
Keywords: PRESENCE, D CHELYDRAE, FRESH WATER TURTLE; CIENCIAS DE LA VIDA; BIOLOGIA ANIMAL; ZOOLOGIA GENERAL